3 - Re-Conceptualizing the Impact of Development on Childcare: The Volta River Project and the Child Survival Challenge in Dzemeni - Kodzo Atakuma Agbodza (African Sociological Review, 2016)
Ghana’s most prestigious energy infrastructural project, the Volta River Project (VRP), aimed to trigger industrial development through the generation of cheap electricity. At its initiation, the project had a people-oriented resettlement and livelihoods restoration programme, which was abandoned. The Tongu Ewe who constituted more than 80 per cent of those displaced, have faced socio-cultural and economic dislocation without adequate compensation. Within the Development-Induced ‘Displacement and Impoverishment’ literature a content and knowledge gap especially theoretical models of the impact on child care. As such, this paper proposes two models that focus on the effects of displacement on childcare practices of impoverished mothers who have assumed multiple roles. This is to establish an understanding of the economic and emotional effects of impoverishment and socio-cultural dislocation from development project displacement as the study in Dzemeni portrays.